2015
DOI: 10.1158/2159-8290.cd-14-0765
|View full text |Cite
|
Sign up to set email alerts
|

TRKing Down an Old Oncogene in a New Era of Targeted Therapy

Abstract: The employment of high-throughput next-generation sequencing techniques in multiple tumor types during the last few years has identified NTRK1, 2, and 3 gene rearrangements encoding novel oncogenic fusions in 19 different tumor types to date. These recent developments have led us to revisit an old oncogene, Trk, (originally identified as OncD), which encodes the TPM3-NTRK1 gene fusion and was one of the first transforming chromosomal rearrangements identified 32 years ago. However, no drug has yet been approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
481
0
28

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 561 publications
(516 citation statements)
references
References 90 publications
7
481
0
28
Order By: Relevance
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No TRKA inhibitors were explored in clinical trials with the possible exception of lestaurtinib (CEP-701), a staurosporine-derivative multikinase inhibitor that was investigated in clinical settings with reported TRKA overexpression, without evidence of efficacy (7,38). However, recent studies that have identified recurring oncogenic NTRK1 rearrangements in subsets of NSCLC and colorectal carcinoma patients (11,12), as well as other studies suggesting a potential role of activated TRKA in other tumor types, including glioblastoma and Spitz melanoma (14)(15)(16)39), have created much renewed interest in the identification and clinical investigation of effective TRKA inhibitors (13). In a rapidly evolving scenario, these findings indicate that TRKA inhibition may represent an innovative opportunity for the therapy of selected patients whose tumors harbor NTRK1 gene rearrangements and this has supported the enrollment of TRKA-positive patients in ongoing clinical trials of entrectinib.…”
Section: Discussionmentioning
confidence: 99%
“…Although an accurate estimation of the frequency of translocation events involving TRKA in either NSCLC or colorectal carcinoma is not yet available due to the low number of cases reported to date, these findings pave the way for targeted therapy with selective TRKA inhibitors in these patients (13). Moreover, in a rapidly evolving landscape, large-scale sequencing efforts have led to identification of additional chromosomal rearrangements involving NTRK1 as well as NTRK2 and NTRK3, the genes which respectively encode the TRKA, TRKB, and TRKC proteins, in further tumor types (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…6,[15][16][17] The NTRK2 fusion gene was first identified in pilocytic astrocytoma, with recent reports of additional fusions including QKI-NTRK2, NACC2-NTRK2, VCL-NTRK2, AGBL4-NTRK2, TRIM24-NTRK2, PAN3-NTRK2, AFAP1-NTRK2, SQSTM1-NTRK2, NAV1-NTRK2, and SLMAP-NTRK2. 6,[15][16][17]41,42 The mechanism of action of these fusion proteins in human gliomagenesis, progression, and drug resistance remains poorly understood. In this study we performed a systematic screen of TK-TELs, which suggested that activated TrkB could transform Ink4a −/− /Arf −/− astrocytes in vivo via upregulation of pSTAT3 signaling and Ccl2 production.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic rearrangement is the most common mechanism of oncogenic activation for this family of receptors, resulting in sustained cancer cell proliferation through activation of MAPK and AKT downstream pathways ( 1 ). Rearrangements of the NTRK1 , NTRK2 , and NTRK3 genes occur across different tumors, including colorectal cancers ( 2 ).…”
Section: Introductionmentioning
confidence: 99%